TEACHERS’ DIFFICULTIES IN ASSESSING STUDENTS’ SPEAKING SKILL USING ONLINE MEDIA DURING ONLINE LEARNING IN SMAN 8 DENPASAR - Ni Luh Kadek Utami Mega; Made Wahyu Mahendra; I Made Iwan Indrawan Jendra (JURNAL IMEDTECH (Instructional Media, Design and Technology), 2022)
COVID-19 pandemic had decrease whole of the world. Many sector, including education sector had to apply online or distance learning. Teachers had to teach their students far from them through online learning media. Thereby, this situation made teachers conducted online assessment. However, online assessment was not the same as assessment as usual, for the new teacher who did not have an experience it had many difficulties and challenges. This study aims at identifying the struggles faced by teachers in assessing students’ speaking skill, factors contributing to the teachers’ difficulties and alternative solutions from teachers to overcome teachers’ difficulties in assessing students’ speaking skill using online media during online learning in SMA N 8 Denpasar. The method of the study was qualitative design with a descriptive approach. In order to collect the data the researcher utilized observation, questionnaire, interview and documentation. The researcher used purposive sampling for choosing the subject. As the result, the researcher found two difficulties faced by teachers in assessing students’ speaking skill using online media, namely intensive and responsive speaking skill. The factors contributing the teachers’ difficulties were internal factors including teachers’ motivation and teachers’ comprehension and external factors including students and facilities. The findings found all of these factors affected to the teachers’ difficulties in assessing students’ speaking skill.